Liquid-Based Cytology and HPV Co-testing in Cervical Cancer Screening for Female Sex Workers: Efficacy and Implications - Rashid, Anum; Atiq, Aribah; Baig, Mohammad Azhar; Chughtai, Akhtar Sohail (Indus Journal of Bioscience Research, 2025)
Introduction: Cervical cancer is a significant global health concern related to persistent high-risk HPV infection. Female sex workers (FSWs) are particularly vulnerable. Despite improved screening and prevention, FSWs in developed countries have a disproportionate risk. Liquid-based cytology (LBC) and HPV co-testing are emerging as promising tools for screening, offering improved sensitivity and specificity compared to conventional cytology alone. This research article aims to address the efficacy of LBC and HPV co-testing in cervical cancer screening. Materials and methods: This cross-sectional study whereby female sex workers (FSWs) in Pakistan aged 20 years and above were screened for cervical cancer using human papillomavirus (HPV) genotyping and Liquid-based cytology (LBC). Results: We collected data from 50 female sex workers. On HPV DNA testing, 6(12%) of them tested positive for HPV DNA, 3(6%) of them had HPV 16 infection, 2(4%) had HPV 52, and 1(2%) had HPV 59 infection. The other 44(88%) tested negative for HPV DNA. On liquid-based cytology, 5(10%) showed LSIL, 1(2%) showed ASC-H, and 1(2%) showed ASC-US. Three of the females who were detected positive for HPV also showed changes in LBC. On comparing both techniques, HPV DNA testing showed 82.14% sensitivity and 84% diagnostic accuracy. However, the P-value was significant for both of the techniques. Conclusion: The conventional pap smear, historically the primary method for cervical cancer screening, has limitations, including inadequate sample collection and low sensitivity. Liquid-based cytology and HPV DNA testing are newer methods with benefits and limitations. Combining methods yields good sensitivity and reduces missed diagnoses, making them valuable screening tools.